Vera. Set 5 [videorecording (DVD)] - Blethyn, Brenda, 1946-; Doughty, Kenny, 1975-; Morrison, Jon; Cleeves, Ann (Acorn, 2015)
With her caustic wit and singular charm, DCI Vera Stanhope and her trusted right-hand man DS Joe Ashworth face a series of captivating murder mysteries set against the breathtaking Northumberland landscape.